Influence of Partial Replacement of Cement and Sand with Coal Bottom Ash on Concrete Properties - Al-Fasih, Mohammed Yahya Mohammed; Mohd Haziman, Wan Ibrahim; Nurul Fasihah, Basirun; Putra Jaya, Ramadhansyah; Mohd Syahrul Hisyam, Mohd Sani (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
An experimental study was accomplished to study the effect of replacement of both cement and sand with coal bottom ash (CBA) on the properties of the concrete. Control mix was prepared without coal bottom ash replacement and nominated as series A. The mixes of series B were prepared with20 % replacement of cement with 30 hours ground coal bottom ash (GCBA). Mixes of series C were prepared with four percentages (5,10,15,20) of CBA as partial replacement of sand. Mixes of Series D mixes were prepared as a combination of series B and C. Slump flow, compressive strength, and water permeability properties were investigated. Series D mixes showed lower workability compared to the series C mixes and control mix. Compressive strength of series D mix gained slightly higher strength compared to the control mix but lower than series C strength. Series C mixes absorbed more water compared to control mix concrete. Series D mixes achieved lower water permeability coefficient compare to series C which showed lower water permeability than the control.